Response of breast cancer cells and cancer stem cells to metformin and hyperthermia alone or combined. - Hyemi Lee; Heon Joo Park; Chang-Shin Park; Eun-Taex Oh; Bo-Hwa Choi; Brent Williams; Chung K Lee; Chang W Song (PLoS ONE)
Metformin, the most widely prescribed drug for treatment of type 2 diabetes, has been shown to exert significant anticancer effects. Hyperthermia has been known to kill cancer cells and enhance the efficacy of various anti-cancer drugs and radiotherapy. We investigated the combined effects of metformin and hyperthermia against MCF-7 and MDA-MB-231 human breast cancer cell, and MIA PaCa-2 human pancreatic cancer cells. Incubation of breast cancer cells with 0.5-10 mM metformin for 48 h caused significant clonogenic cell death. Culturing breast cancer cells with 30 µM metformin, clinically relevant plasma concentration of metformin, significantly reduced the survival of cancer cells. Importantly, metformin was preferentially cytotoxic to CD44(high)/CD24(low) cells of MCF-7 cells and, CD44(high)/CD24(high) cells of MIA PaCa-2 cells, which are known to be cancer stem cells (CSCs) of MCF-7 cells and MIA PaCa-2 cells, respectively. Heating at 42°C for 1 h was slightly toxic to both cancer cells and CSCs, and it markedly enhanced the efficacy of metformin to kill cancer cells and CSCs. Metformin has been reported to activate AMPK, thereby suppressing mTOR, which plays an important role for protein synthesis, cell cycle progression, and cell survival. For the first time, we show that hyperthermia activates AMPK and inactivates mTOR and its downstream effector S6K. Furthermore, hyperthermia potentiated the effect of metformin to activate AMPK and inactivate mTOR and S6K. Cell proliferation was markedly suppressed by metformin or combination of metformin and hyperthermia, which could be attributed to activation of AMPK leading to inactivation of mTOR. It is conclude that the effects of metformin against cancer cells including CSCs can be markedly enhanced by hyperthermia.